Concurrent Enrollment in the Student Voice. Issue 12 (2nd December 2022) - McGowan Bucci, Katie; Simpson, Amber
ABSTRACT: Objective: Concurrent enrollment programming is on the rise in the United States. Offering authentic college coursework to high school students has been shown to increase college enrollment, persistence, and graduation, as well as cut down on cost and time to degree. This study provides perspectives on concurrent enrollment directly from students. A conceptual framework using college student identity centrality is introduced. Method: Utilizing semi-structured interviews to form an instrumental, collective case study, undergraduate college students with a prior concurrent enrollment history provided their perspective on embarking on college while in high school. Results: From the data, it was concluded that concurrent enrollment serves as a "taste of college" (Lily); concurrent enrollment helps students to shape their future plans, often allowing them to pursue additional educational opportunities due to early-earned credit; and early exposure to college showed promise at helping students adopt an earlier college student identity. Contributions: This study addresses a gap in the literature in understanding concurrent enrollment from the student perspective. The study supports findings in recent research that suggest early exposure to and practice of college increases college readiness as well as self-efficacy. In addition, this study suggests the need for further research in understanding concurrent enrollment student perspectives from a diverse sample, as well as adopting a conceptual lens to study concurrent enrollment as a mechanism by which students can develop a college student identity.